2018
DOI: 10.4274/jtgga.2017.0115
|View full text |Cite|
|
Sign up to set email alerts
|

Short-term results of the efficacy of percutaneous tibial nerve stimulation on urinary symptoms and its financial cost

Abstract: Objective:Overactive bladder (OAB) affects 16.9% of women in the United States. Percutaneous tibial nerve stimulation (PTNS) is a third-line treatment for patients who are refractory to behavioral and pharmacologic therapies. We aimed to evaluate the effects of PTNS on urinary symptoms in patients diagnosed as having refractory OAB and investigate the cost of medications and clinical visits before and after PTNS treatment.Material and Methods:We reviewed 60 women with refractory OAB treated with PTNS. Episodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The findings of this study corroborate those of a previous retrospective study in which 24 elderly patients, with a mean age of 70.25±11.14 years, received 30 minutes of percutaneous tibial nerve stimulation once a week for 12 weeks and showed a reduction of urgency episodes, urge urinary incontinence and nocturia (16). In a previous retrospective study, 62 women with OAB, with a mean age of 72.7 years, underwent 12 sessions of percutaneous tibial nerve stimulation and presented a decrease in urgency and urge urinary incontinence episodes (17); therefore, the electrical stimulation of the tibial nerve seems to be effective in the treatment of OAB in adults and elderly people.…”
Section: ' Discussionsupporting
confidence: 90%
“…The findings of this study corroborate those of a previous retrospective study in which 24 elderly patients, with a mean age of 70.25±11.14 years, received 30 minutes of percutaneous tibial nerve stimulation once a week for 12 weeks and showed a reduction of urgency episodes, urge urinary incontinence and nocturia (16). In a previous retrospective study, 62 women with OAB, with a mean age of 72.7 years, underwent 12 sessions of percutaneous tibial nerve stimulation and presented a decrease in urgency and urge urinary incontinence episodes (17); therefore, the electrical stimulation of the tibial nerve seems to be effective in the treatment of OAB in adults and elderly people.…”
Section: ' Discussionsupporting
confidence: 90%
“…Due to differences in health-care systems across countries, the reported costs vary. For instance, Kurdoglu et al [45] reported that third-line PTNS in Texas reduced the costs of medications, physician and nurse visits in OAB patients. Despite the financial advantages, PTNS was not commonly utilized among patients undergoing third-line treatment for OAB.…”
Section: Financial Aspects Of Ptns In Modern Health-care Systemsmentioning
confidence: 99%